AN ANALYSIS OF FLOUTING MAXIM IN ANIMATED MOVIE THE EMPEROR’S NEW GROOVE: A PRAGMATIC APPROCH - Sitinjak, Lasmaida; Saragi, Christina Natalina; Manurung, Lastri Wahyuni (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research discusses a pragmatic study, focusing on the film "Animated Movie The Emperor's New Groove" and its maxims violations. Knowing the types of maxims that are ignored and the dominant flouting     often committed by characters in films is the objective of this study. Grice's Theory (1975) is used in this research. Here, the researchers used a qualitative descriptive method. With observation, data is collected. These actions consist of watching the movie "Animated Movie the Emperor's New Groove" and then observing discussions where the maxims are violated.The research results show that there are four types of maxims found in the film. The total data is 80 data points that violate. 36 (45%) maximum violation data Quantity, 11 (14%) maximum violation data Quality, 12 (15%) data on maximum relationship violations, 9 (11%) data on maximum method violations. From the results found by the researchers, the maxim most frequently violated is the Maxim of Quantity, which was violated 36 times (45%). Violating a maxim means that the speaker cannot adhere to the maxim correctly. Maxim violations occur because the speaker deliberately does not adhere to the maxim. The reasons for using maxims violations in films also vary, such as ignoring the interlocutor's statements, providing excessive information, trying to change the topic of conversation to make it irrelevant, and causing the interlocutor to think ambiguously about what the speaker means.